2013
DOI: 10.1590/s1516-89132013000200016
|View full text |Cite
|
Sign up to set email alerts
|

Histology and ultrastructure of the fat body of Anticarsia gemmatalis (HÜBNER, 1818) (LEPIDOPTERA: NOCTUIDAE)

Abstract: The aim of this study was to analyze the morphologically the fatty body of fourth-instar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Thus, Plodia interpunctella Hübner (Shirk and Malone 1989) shows one dark-colored fat body located in the posterior part of the abdomen, and another whitish one in its anterior part; whereas Helicoverpa zea (Boddie) (Haunerland and Shirk 1995) presents a parietal fat body in the anterior part of the abdomen, its color being lighter than that of the previsceral when treated with hematoxiline-eosine. In Anticarsia gemmatalis Hübner (Carvalho et al 2013), however, two fat bodies, one parietal and one perivisceral, can be observed. The former is underneath the tegument and beside the digestive tube, with an irregular distribution between the thorax-abdomen regions, and the latter is beside the digestive tube.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, Plodia interpunctella Hübner (Shirk and Malone 1989) shows one dark-colored fat body located in the posterior part of the abdomen, and another whitish one in its anterior part; whereas Helicoverpa zea (Boddie) (Haunerland and Shirk 1995) presents a parietal fat body in the anterior part of the abdomen, its color being lighter than that of the previsceral when treated with hematoxiline-eosine. In Anticarsia gemmatalis Hübner (Carvalho et al 2013), however, two fat bodies, one parietal and one perivisceral, can be observed. The former is underneath the tegument and beside the digestive tube, with an irregular distribution between the thorax-abdomen regions, and the latter is beside the digestive tube.…”
Section: Resultsmentioning
confidence: 97%
“…In Lutzomyia longipalpis (Lutz & Neiva, 1912) (Diptera: Psychodidae) and Phlebotomus papatasi (Scopoli, 1786) (Diptera: Psychodidae), it was observed that glycogen accumulation was higher in PV fat body cells after feeding the flies with sugar (Assis et al, 2014). Although the PF and PV fat bodies of the caterpillar Anticarsia gemmatalis Hübner, 1818 (Lepidoptera: Erebidae) have different roles, it has been stated that both of them were involved in the synthesis of lipids and other substances (Carvalho et al, 2013). In our study on B. orientalis, we observed that larger lipid droplets were stored in the PF fat body while more protein granules and glycogen were deposited in the PV fat body similar to the results reported by Dean et al (1985) and Haunerland & Shirk (1995).…”
Section: Discussionmentioning
confidence: 99%
“…These are peripheral (PF) fat body located below the integument and perivisceral (PV) fat body, observed around the digestive tract (Resh & Carde, 2003;Lipovsek & Novak, 2016). These two regions can have different lipid, glycogen, and protein densities (Carvalho et al, 2013). It has been suggested that lipid synthesis and storage occur mainly in PF fat body, whereas PV fat body is associated with protein synthesis and storage in various insects (Dean et al, 1985;Roma et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These two regions may differ from each other in shape as well. While the PF fat body is in the form of a cylindrical cell layer, the PV fat body is formed by cell clusters (Carvalho et al, 2013). In B. orientalis , PF fat body possessed one or several rows of cells under the integument, while PV fat body had cell clusters around the midgut, hindgut and gonads.…”
Section: Discussionmentioning
confidence: 99%